Percepção ambiental de uma comunidade nova católica frente à eficiência da aplicação da fitorremediação de um córrego urbano - Lima, Luiza Raquel Fernandes (2019)
Most urban aquatic environments are highly eutrophic due to nutrient input from poor sanitation systems. In this way, they no longer provide important ecosystem services to society. Thus, it is essential to carry out aquatic restoration work, so that these ecosystems can again present their potential as ecosystem service providers. In assessing the environmental perception of members of the Doce Mãe de Deus Community (DMDC), only 38% knew the name of the Cuiá River. It was found that of those who have cesspools in their homes, 70% never filled. In order to increase the environmental sensibility of the members of the CDMD, lectures were held, as well as the construction of an ecological cesspool Banana tree circle, for the treatment of grey waters, which were previously thrown into the environment. In order to contribute to the improvement of water quality of urban rivers, this research aimed to test the use of phytoremediation in an urban stream that transports open sewage. For this purpose, physical and chemical analyzes of the water quality of the stream that crosses the DMDC, located in the Geisel, in the entrance and out of it, before and after the insertion of the biotreatment were performed. Nitrogen and orthophosphate compounds, dissolved oxygen, pH, conductivity, oxi-reduction potential, total dissolved solids and temperature variables were analyzed. The results allowed to verify the effectiveness of phytoremediation in the treatment of sewage polluted waters and found the removal of 81 mg phosphate and 52 mg nitrate in each m3 of water that would enter the Cuiá River, thus preventing further eutrophication. With the exception of ammonia and nitrite, which did not show significant differences before and after the installation of biotreatment, all others showed improvement in environmental quality. It is concluded from this research that the use of phytoremediation in urban streams that carry sewage can be very efficient in improving water quality, increasing the self-purification capacity in these and their receiving bodies, at low cost.